Analisis Kesulitan Belajar Mahasiswa Teknik Informatika pada Mata Kuliah Fisika Dasar: Analysis of Learning Difficulties of Informatics Engineering Students in Basic Physics Courses - Tita Puspitasari (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to determine several factors that cause difficulties experienced by Informatics Engineering Students at Pamulang University in studying the material in the Basic Physics course. The research method used in qualitative descriptive research where the data taken using interview techniques related to learning difficulties faced by students and the results of student tests from several basic physics lecture materials such as vector resultants with a percentage of students experiencing difficulties of 96.87%, particle motion dynamics 87.50%, conservative force 90.65%, waves 78.16%, and electricity mustsn 62.50%, where the data taken came from 1st semester students of the Informatics Engineering study program at Pamulang University. The results showed that students' learning difficulties in understanding the materials in the introductory physics course were caused by several factors, including weak mastery of basic mathematics, low understanding of physics material concepts, low learning motivation, less than optimal fighting spirit, and also lack of independent practice of basic physics questions outside of lecture assignments. Based on the results of the data, providing motivation and reinforcement of the material more intensively at each lecture meeting is a note to lecturers so that they can continue to increase interest, raise motivation and fighting spirit of students in understanding fundamental physics material and lecturers need to create strategies for lecture activities to be more interesting to students so that they can also improve learning outcomes optimally.